Auditoria regular municipio de Cordoba Quindío vigencia 2012 (2013)
The regular audit is the review and the examination performed in audit institutions superior to processes of different nature, which make the different agencies of central, state and local government in the compliance of its legal powers that aim to issue a judgment on the efficacy, efficiency and profitability meeting the objectives of the state entity under review in order to monitor public management and safeguard the society’s rights. In the particular case of this current internship, it will be carried out a regular audit to the town Cordoba for 2012, based on the territorial audit guide (GAT) , in such an attainment it will be taken into account each audit phase ;it will be started by the planning stage in which it will be known and verified all the information given on the physical and magnetic through SIA and COVI application , where by means of verification it may be determined the flaws that occur in the information provided . The execution stage concerns the confirmation and verification of the information regarding the control subject, where it will be established and verified the compliance of each of the processes designed by the entity and that are contained in the guidelines of the legal frameworks that they confer upon. Finally, in the report phase, it will be released the results of the development of the previous phases, in order to give a unified outlook formed by the judgment of the financial statements and the concept on the management and the outcomes.